Membebaskan Yang Tertindas: Peran Gereja Dalam Perspektif Gustavo Gutierrez Terhadap Kemiskinan - Tataung, Nadia; Palar, Yolanda N. (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2024)
One of the major issues faced by the global community, including in developing countries such as Indonesia, is poverty. A renowned theologian from Latin America, Gustavo Gutiérrez, developed the concept of liberation theology, which emphasizes the active role of the church in combating poverty and social injustice. The findings of this research show that Gutiérrez's liberation theology provides a strong conceptual framework for the church to act as an agent of social change in liberating the oppressed from poverty. Gutiérrez asserts that the church is not only a place of worship but also a place for supporting and advocating for the rights of the poor. In practice, liberation theology is applied in churches through various social, educational, and economic programs to address the root causes of poverty and empower impoverished communities. The conclusion of this research is that the role of the church, from the perspective of Gutiérrez's liberation theology, is crucial in the struggle to liberate the poor from the shackles of poverty. Churches that implement this theology demonstrate their success in achieving sustainable and significant social change. Therefore, this research provides important theoretical and practical contributions to the study of theology and religious practice. Theoretically, this research enriches the discourse on liberation theology and the social role of the church. Practically, this research offers guidelines for churches in developing effective programs to tackle poverty.